2018
DOI: 10.1021/acs.macromol.8b01888
|View full text |Cite
|
Sign up to set email alerts
|

Method for the Synthesis of γ-PEGylated Folic Acid and Its Fluorescein-Labeled Derivative

Abstract: This paper reports exclusive γ-conjugation of poly­(ethylene glycol) (PEG) to folic acid (FA) and the synthesis of its fluorescein (Fl)-labeled derivative. FA is first reacted with 1 equiv of n-BuLi that forms the metal salt exclusively at the γ-position. Model reactions between γ-lithiated FA and bromo-alcohols were used to demonstrate exclusive γ-conjugation. γ-PEGylated FA was then synthesized by reacting γ-lithiated FA with a bromine-functionalized methoxy-PEG (Br-PEGM) that is prepared by Candida antarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…PEG 1000 -dithiol was obtained by reacting PEG 1000 -monothiol with fresh CALB and MP-SH for 24 h. PEG 2050 -monothiol was formed in 16 h, and dithiol formation required additional CALB and MP-SH. Based on our data, it can be concluded that enzyme catalyzed transesterification is a convenient and green method to effectively synthesize PEG mono-and di-thiols that are suitable candidates for thiol-ene click reactions and Michael addition type of reactions [4].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…PEG 1000 -dithiol was obtained by reacting PEG 1000 -monothiol with fresh CALB and MP-SH for 24 h. PEG 2050 -monothiol was formed in 16 h, and dithiol formation required additional CALB and MP-SH. Based on our data, it can be concluded that enzyme catalyzed transesterification is a convenient and green method to effectively synthesize PEG mono-and di-thiols that are suitable candidates for thiol-ene click reactions and Michael addition type of reactions [4].…”
Section: Discussionmentioning
confidence: 77%
“…Poly(ethylene glycol) (PEG) is the most frequently used polymer for biomedical research and applications because it is soluble in organic as well as aqueous media [1], is not cytotoxic and immunogenic [2], and is easily excreted from living organisms [3]. Click chemistries and Michael addition reactions are often used for PEGylation of drugs to make them more water soluble [4]. Thiol-functionalized PEGs have an important role in these reactions [5][6][7][8][9][10] and can be used as a 'Michael donor' or in thiol-ene click reactions to synthesize conjugates for targeted drug delivery [7].…”
Section: Introductionmentioning
confidence: 99%
“…A polymeric DDV composed of fluorescein (FL) and exactly two FA attached to a central PEG molecule was synthesized to target overexpressed FRs in neoplastic cells (Puskas et al, ). FA served as a ligand for the overexpressed cell surface FRs, which is internalized through receptor‐mediated endocytosis.…”
Section: Methodsmentioning
confidence: 99%
“…First, diamine‐terminated poly(ethylene glycol) (H 2 N‐PEG‐NH 2 ) ( M n = 2,000 g/mol) underwent a Michael addition with two moles of fluorescein diacrylate (FLDA) in the presence of Candida antarctica Lipase B (CALB) yielding Acrylate‐FL‐PEG‐FL‐Acrylate ( M n = 2,880 g/mol). Then a second Michael addition was carried out with two moles of thiol‐functionalized folic acid (FA‐γ‐SH) to get the folic acid end groups, as reported (Puskas et al, ). This synthetic methodology allows the replacement of fluorescein with a functional group to which doxorubicin (DOX) can be conjugated: FA‐(DOX)‐PEG‐(DOX)‐FA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation